Perdas de água e solo por erosão em simulador de chuvas de um Latossolo argiloso submetido a níveis de compactação - Castro, Mayra Beatriz Semiano (2024)
Soil physical quality is affected by soil use and management. With the increasing adoption of heavy agricultural machinery, soil degradation problems such as compaction and water erosion have been intensified. Thus, the objective of this work was to evaluate the influence of compaction levels of a clayey Oxisol, slopes and rainfall duration, on water and soil losses by erosion and on the runoff coefficient in a rain simulator. This study was carried out at the Universidade Estadual do Oeste do Paraná, next to the soil physics laboratory. The rain simulator has a mobile box with dimensions of 1.0 x 1.0 x 0.30 m. Rainfall intensity was fixed at 34 mm.h-1 with duration times of 10, 20 and 30 min. Four compaction levels were used with soil densities of: 1.1; 1.2; 1.3 and 1.4 Mg.m-3 and four slope levels of the ramp: 6, 9, 12 and 18%. Soil compaction was performed artificially in the 0.10-0.20 m layer, to simulate field conditions, in which this is usually the layer that presents physical restrictions due to concentrating the stresses imposed by the traffic of machines and implements agricultural. The rates of water and soil losses were monitored, collecting the runoff volume in the simulator's gutter and quantifying soil and water losses. The experimental design was completely randomized, in a factorial arrangement, with four replications for each evaluated condition (compaction level x ramp slope). Losses of water and soil by erosion, as well as the runoff coefficient, were more intensely affected by soil density in relation to the ramp slope as the duration of the rain increased, showing that when the soil has a high level of compaction the ramp slope is less determinant in soil water losses by erosion. However, at low soil density values (up to 1.2 Mg.m-3), water and soil losses were more influenced by the ramp slope. "This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001"